2019
DOI: 10.1093/scan/nsz032
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cerebellum in reconstructing social action sequences: a pilot study

Abstract: Recent research has revealed that the cerebellum plays a critical role in social reasoning and in particular in understanding false beliefs and making trait attributions. One hypothesis is that the cerebellum is responsible for the understanding of sequences of motions and actions, which may be a prerequisite for social understanding. To investigate the role of action sequencing in mentalizing, we tested patients with generalized cerebellar degenerative lesions on tests of social understanding and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 47 publications
14
98
0
Order By: Relevance
“…On the other hand, most standard social cognition tests cannot detect social impairments in cerebellar cohorts because cerebellar patients' symptoms are present in selective domains. In this view, the implementation of specific tasks involving complex and abstract forms of mentalizing [66] will help to detect such a relation in greater patients population. Another issue that merits to be discussed concerns with the possible cortical involvement in symptomatic SCA2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most standard social cognition tests cannot detect social impairments in cerebellar cohorts because cerebellar patients' symptoms are present in selective domains. In this view, the implementation of specific tasks involving complex and abstract forms of mentalizing [66] will help to detect such a relation in greater patients population. Another issue that merits to be discussed concerns with the possible cortical involvement in symptomatic SCA2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…To provide further support for cerebellar specificity in generating appropriate social action sequences, Van Overwalle and colleagues [ 3 ] described impaired abilities in patients affected by cerebellar degenerative disease when performing a sequential version of a false belief task [ 76 ]. Taking into account this evidence, it can be conceptualized that the cerebellum is a unique predictive structure in different domains.…”
Section: The Cerebellum and Mind Readingmentioning
confidence: 99%
“…These reports focused on the understanding of affect in facial expressions of others [ 1 ] without much attention to higher-level mental states of others. However, a novel collaboration between researchers from the field of social neuroscience (Frank Van Overwalle) and the cerebellum (Peter Marien and Mario Manto) resulted in the discovery of the important social function of the cerebellum [ 2 , 3 ] which instigated novel research on the potential role of the cerebellum in social cognition. Social cognitive processes encompass social “mentalizing” (or mind reading) which depends on the inferred unobserved mental state of other people as well as social “mirroring” (or body reading) which depends on the observed goal-directed body movement of others.…”
Section: Introduction and Evolutionary Pastmentioning
confidence: 99%
“…With respect to understanding social behavior, several studies reported that CB patients have impairments in identifying or generating a plausible sequence of pictures reflecting a complex action performed by a human agent [111,112]. Patients were particularly impaired when correct sequencing required mentalizing about the agents' beliefs, but not so for routine social scripts [113]. Likewise, Zalla and colleagues [114,115] found that children with autism spectrum disorder (ASD) were impaired in predicting the outcome or sequence of human behavior, but were less impaired in understanding routine social interactions.…”
Section: Relationship To Ccas: Do Patient Outcomes Reflect Imaging Pamentioning
confidence: 99%